WEB BASED LABORATORY TASK-SUBMITTER APPLICATION MODEL - Soetam Rizky Wicaksono (Universitas Ahmad Dahlan, 2010)
Teaching learning process in laboratory is obligatory in engineering education especially for course in information technology (IT). To make laboratory activities become more interesting for the students, lecturers must build application-based exercise for the student, but after students accomplished their short exercise, it is found that lecturers got difficulty to compile and grade all the exercises. This paper is based on the idea how to overcome the problem above, in order to make activities in the laboratory comfortable for both lectures and student. It is expected that the lectures will able to fully control all practical activity and save the time automatically. To make approach to solve the problem in IT, a modeling process must be conducted first. There for, firstly, this paper explain the model approach for the problem above, then the IT design for practices in laboratory is described. The IT design to overcome the problem has been effectively applied in the real teaching learning process.